A ROLE OF DEPARTMENT OF INSTITUTION OF HIGHER LEARNING IS IN FORMING OF HEALTHY WAY OF LIFE OF STUDENTS - Николай Алексеевич Лопатин (Медицина в Кузбассе)
An idea is offered in the article, to examine the department of physical education of institution of higher learning as center of healthy way of life of students, because the problem of worsening of physical, psychical and moral health of students is intensifyed and complicated by the socio-economic crisis and active transformation processes prolonged in Russia both on the whole in society and concretely in the system of higher education. Leaning against carried out researchers numerous questioning and got by them data, the necessity of search of ways and forms of forming, maintenance and development of health of students of institution of higher learning is grounded in the article. A labour-market requires a competent specialist not only professionally but also healthy, creatively active and dynamic in the professional development, that does the problem of healthy way of life more actual and sharp for the modern system of higher education.